2012
DOI: 10.1371/journal.pone.0039766
|View full text |Cite
|
Sign up to set email alerts
|

Myoferlin Depletion in Breast Cancer Cells Promotes Mesenchymal to Epithelial Shape Change and Stalls Invasion

Abstract: Myoferlin (MYOF) is a mammalian ferlin protein with homology to ancestral Fer-1, a nematode protein that regulates spermatic membrane fusion, which underlies the amoeboid-like movements of its sperm. Studies in muscle and endothelial cells have reported on the role of myoferlin in membrane repair, endocytosis, myoblast fusion, and the proper expression of various plasma membrane receptors. In this study, using an in vitro human breast cancer cell model, we demonstrate that myoferlin is abundantly expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 51 publications
7
71
1
Order By: Relevance
“…One of the most striking biologic effects observed here was the inability of breast cancer cells to respond to EGF-stimulus to migrate (MDA-MB231 and MDA-MB468) or undergo EMT (MDA-MB468). Li and colleagues (14) reported recently that MDA-MB231 underwent a spontaneous reverse EMT in the absence of myoferlin. However, similar data published by the same authors elsewhere (38) MB231 cells as shown in ref.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the most striking biologic effects observed here was the inability of breast cancer cells to respond to EGF-stimulus to migrate (MDA-MB231 and MDA-MB468) or undergo EMT (MDA-MB468). Li and colleagues (14) reported recently that MDA-MB231 underwent a spontaneous reverse EMT in the absence of myoferlin. However, similar data published by the same authors elsewhere (38) MB231 cells as shown in ref.…”
Section: Discussionmentioning
confidence: 99%
“…S5). Interestingly, Li and colleagues (14) and Eisenberg and colleagues (13) both showed that short hairpin RNA (shRNA)-mediated myoferlin depletion impairs MDA-MB231 cells' invasion; however, it has no effect on cell migration or proliferation. Our invasion and proliferation data are in agreement with the literature (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, myoferlin was found to be important for breast cancer invasion. [13][14][15] Our laboratory showed that myoferlin, is a key regulator of EGFR activity in human breast cancer cells. 16 Interestingly, it was reported, in a Kaplan-Meier survival curve, that patients with myoferlin-positive PDAC had a significant lower overall survival than those with a myoferlinnegative tumor.…”
mentioning
confidence: 99%